"I didn't know what to expect or What to do": Impacts of a severe winter storm on residents of subsidized housing in Texas. (January 2023) - Li, Dongying; Zhang, Yue; Li, Xiaoyu; Meyer, Michelle; Bazan, Marissa; Brown, Robert D.
Abstract: Residents of public or subsidized housing experience social and environmental disadvantages and are therefore particularly vulnerable to disasters. Although research has highlighted risks associated with common disasters, such as floods and heatwaves, to date little is known about the impacts of infrequent disasters, such as a winter storm in a subtropical climate with mild winter weather. Even less is known about factors related to disaster preparation by and coping strategies of these disadvantaged residents. The present study aimed to examine the impacts of the 2021 Winter Storm Uri on subsided housing residents and the factors that enabled or hindered their effective adaptation. We conducted semi-structured interviews two to four months post-disaster with residents from eleven subsidized housing sites in College Station, Texas. A total of 33 participants aged between 24 and 90 completed the interviews. Guided by relevant theories such as the Protective Motivation Theory (PMT), a combination of inductive and deductive coding was carried out using MaxQDA qualitative data analysis software, and codes, themes, and categories were identified reiteratively. The results demonstrated the process involving cognitive appraisal, preparation intention, and behavioral adaptation and the roles played by environmental stressors and infrastructural modifiers in subsidized housing. Specifically, we found: 1) insufficient risk communication and the digital divide hindered formation of accurate hazard appraisal, 2) high perceived costs of preparation contributed to low coping appraisal, 3) Differences in physical infrastructure conditions were linked to varying adaptation capacities and behaviors, and 4) overall social isolation was partly remedied by clustered social ties formed within neighborhoods that were homophily. The implications for future disaster policy and planning are discussed.